Geo-Environmental Spatial Imaginaries: Reframing Nature Using Soft Spaces and Hybrid Rationalities - Tippett, Joanne; Deas, Iain; Haughton, Graham (Frontiers in Sustainable Cities, 2022)
This article introduces the idea of hybrid rationalities as a complement to and extension of existing scholarship on hybrid governance and hybrid infrastructure. The research presented here also contributes to work on soft spaces and spatial imaginaries, which has mainly focused on planning and regeneration, by extending consideration to geo-environmental imaginaries and environmental soft spaces. A case study of the Mersey Belt region, which stretches between Manchester and Liverpool in England, reveals the ways in which multiple forms of new rationalities have been absorbed into the work of those looking to promote strategic environmental thinking that works at landscape scale, that is above the level of the individual site. In the process, multiple new geo-environmental spatial imaginaries have been created as part of the process of attracting funders and stakeholders. These new spatial imaginaries have been accompanied by experiments in creating new environmental soft spaces, supported by increasingly hybridized forms of governance in which the roles and rationalities of different stakeholders have to some extent blurred. In the process, actors have shaped, and shared distinctive understandings of how projects to support nature can be used to support wider goals such as addressing climate change, economic regeneration and social well-being.